(untitled) (European Journal of Health Research, 2022)
The acquired pneumonia community is one of the most common causes of hospital admissions, with high impact on mortality. The objective was to evaluate the association of various factors with the state of severity at admission in patients hospitalized for pneumonia. It was done a descriptive study with 1,809 patients hospitalized for pneumonia between 2012 and 2020. Factors related to the patient, the disease, and prehospital management were evaluated as independent variables; as a dependent variable, the status at admission was considered. Through bivariate and multivariate analysis, the association was measured through the odds ratio and its 95% confidence interval. It was showed association significant among various conditions and evaluated the state of gravity entry; the factors that showed the greatest strength of association were: bedridden (OR 5.4 [4.2;7]) , presence of a medium or large pleural effusion (OR 4.8 [3.2; 7.2] ) , age of 60 or more (OR 4.2 [3.5,7]), extension nonlocal a radiation lobe (OR 3.6 [2.8;4.6] ) and a history of advanced dementia (OR 2.2 [1.7,2.8]). As conclusions, there is a relationship between the occurrence of the state of severity of patients with community-acquired pneumonia at the time of their hospital admission and several adverse conditions, some inherent to the characteristics of the patients (previous bedridden, advanced dementia and diabetes mellitus) and others to the radiological behavior of the disease (the radiological extension of the affectation beyond one lobe and the presence of a medium or large pleural effusion at the time of admission).